History of mental disorders and leukocyte telomere length in late adulthood: The Helsinki Birth Cohort Study (HBCS) - Savolainen, Katri; Räikkönen, Katri; Kananen, Laura; Kajantie, Eero; Hovatta, Iiris; Lahti, Marius; Lahti, Jari; Pesonen, Anu-Katriina; Heinonen, Kati; Eriksson, Johan G. (Journal of psychiatric research, 2012)
Shorter leukocyte telomere length (LTL) has been linked with mental disorders and with other manifestations of chronic non-communicable diseases. Mental disorders are associated with increased morbidity and premature mortality. It remains unclear if shorter LTL characterizes patients who have been diagnosed with mental disorders in the past, and who have survived till late adulthood. 1051 women and 905 men of the Helsinki Birth Cohort Study participated in this study. LTL was measured by using the real-time quantitative PCR method for subjects and patients at the mean age of 61.5 years. Patients with a mental disorder severe enough to warrant hospitalization (n = 116) were identified by their case records in the Finnish Hospital Discharge Register and the use of psychotropic medication by reimbursement entitlements or prescription fills (n = 665) data in the Finnish Social Insurance Register. Participants hospitalized for any mental or substance use disorders had longer LTL than non-hospitalized controls (p-values < 0.042). Moreover, only those any mental disorder patients who had psychotropic medication use had longer LTL than non-hospitalized controls (p = 0.02). Adjustment for a number of covariates did not attenuate the association. Our findings suggest that shorter LTL may not be an intrinsic feature of mental disorders. Future research is needed to elucidate if psychotropic medication is involved in leukocyte telomere length maintenance in subjects with mental disorders.